2020
DOI: 10.1038/s41598-020-64060-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo large-scale analysis of Drosophila neuronal calcium traces by automated tracking of single somata

Abstract: How does the concerted activity of neuronal populations shape behavior? impediments to address this question are primarily due to critical experimental barriers. An integrated perspective on large scale neural information processing requires an in vivo approach that can combine the advantages of exhaustively observing all neurons dedicated to a given type of stimulus, and simultaneously achieve a resolution that is precise enough to capture individual neuron activity. current experimental data from in vivo obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…In comparison to those data, using genetic and functional identification of PN subsets we reveal here that the structural modifications are specific and limited to the PNs conveying the conditioned odour. Importantly, our in vivo functional imaging data support the view that the circuit reorganization that we describe leads to additional [65]. If we hypothesize that appetitive conditioning could lead to a similar outcome, our data could provide anatomical and functional support to these findings.…”
Section: Resultssupporting
confidence: 84%
“…In comparison to those data, using genetic and functional identification of PN subsets we reveal here that the structural modifications are specific and limited to the PNs conveying the conditioned odour. Importantly, our in vivo functional imaging data support the view that the circuit reorganization that we describe leads to additional [65]. If we hypothesize that appetitive conditioning could lead to a similar outcome, our data could provide anatomical and functional support to these findings.…”
Section: Resultssupporting
confidence: 84%
“…A recent publication, however, suggests an exciting alternative view. After aversive LTM establishment, the number of KCs responding to the conditioned odor is increased (Delestro et al, 2020). If we hypothesize that appetitive conditioning leads to a similar outcome, our data could provide anatomical and functional support to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have observed an increased representa- tion of stimuli in KCs which was mediated through electrical synapses [49]. Furthermore, conditioning induced a functional decorrelation of calcium traces in KC lobes [6,15]. In short, KCs could be recruited to participate in the representation of a stimulus and increase their synaptic input while on the other hand synaptic modulations can decrease synaptic input at the KC-MBON synapse.…”
Section: Discussionmentioning
confidence: 99%